ASYMPTOTIC BEHAVIOR OF INFINITE PRODUCTS OF PROJECTION AND NONEXPANSIVE OPERATORS WITH COMPUTATIONAL ERRORS - Pustylnik, E.; Reich, S.; Zaslavski, A. J. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2012)
We study the asymptotic behavior of infinite products of orthogonal projections and other (possibly nonlinear) nonexpansive operators in Hilbert space in the presence of computational errors.